The Influence of Digital Marketing, Product Quality, and Perceived Value on Purchase Intention - Dhea Putri Ashari; R.A Nurlinda (The Future of Education Journal, 2026)
This study aims to examine and analyze the effects of digital marketing, product quality, and perceived value on consumers' purchase intention toward Skintific skincare products, as well as to identify the most dominant factor influencing purchase intention. The study employed a quantitative approach. The sample consisted of individuals aged 17 years and above who were familiar with Skintific skincare products, had been exposed to Skintific digital marketing activities (live streaming or digital content), and resided in the Greater Jakarta area (Jabodetabek). A total of 170 valid questionnaires were collected and analyzed using multiple linear regression. The findings indicate that digital marketing, product quality, and perceived value simultaneously have a positive and significant effect on purchase intention toward Skintific skincare products. Partially, each variable digital marketing, product quality, and perceived value also exerts a positive and significant influence on purchase intention. Furthermore, perceived value was identified as the most dominant factor affecting consumers’ purchase intention. These findings support consumer behavior theory, which suggests that digital marketing, product quality, and perceived value are important determinants of purchase intention. Digital marketing and product quality represent elements of the marketing mix, whereas perceived value reflects a psychological factor influencing consumer purchasing decisions.